Implementation of the Let's Read Smart Challenge in Improving Third Grade Students' Reading Interest in Elementary School - Dianita Rahmawati; Choirun Nisa (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to analyze the implementation of literacy management through the Let's Read Smart Challenge program as an effort to foster reading interest among third-grade students at SD Negeri Bibis Luhur I Surakarta. This program is designed as a technology-based learning innovation that combines literacy management with digital media that is attractive and easily accessible to students. Through reading challenge activities, students are encouraged to enjoy reading independently while fostering enjoyable and sustainable literacy habits.Methodology: This study uses a qualitative approach with a case study method. The research subjects consisted of the principal, classroom teachers, and third-grade students. Data collection was conducted through observation, in-depth interviews, and documentation. The data were analyzed using Miles and Huberman's interactive analysis model, which includes data reduction, data presentation, and conclusion drawing. Data validity was obtained through triangulation of sources, techniques, and time to ensure the credibility of the research results.Results: The results show that the Let's Read Smart Challenge program effectively increases students' interest in reading. Before the program was implemented, students tended to be less interested in reading. After implementation, students became more enthusiastic, actively discussed, and showed independence in choosing and understanding digital reading materials. The success of the program was supported by the leadership of the principal, teacher training, the availability of digital facilities, and parental support.Applications/Originality/Value: This study contributes to the development of digital literacy management in elementary schools. The Let's Read Smart Challenge program is an effective innovative model for building a fun and sustainable literacy culture and encouraging students' critical thinking skills and motivation to learn in the digital age.